2012
DOI: 10.2147/dddt.s39541
|View full text |Cite
|
Sign up to set email alerts
|

Single early instillation of mitomycin C and urinary alkalinization in low-risk non-muscle-invasive bladder cancer: a preliminary study

Abstract: BackgroundThe purpose of this study was to determine the effectiveness of a single early instillation of mitomycin C (MMC) after transurethral resection of bladder tumor (TURBT) together with urinary alkalinization in patients with low-risk non-muscle-invasive bladder cancer (NMIBC).MethodsBetween February 2006 and November 2010, patients diagnosed as having a primary bladder tumor were randomized into standard and optimized treatment groups. The treatment groups were formed prospectively from patients with NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…2. The prospective study of Ersoy et al (87), showed no recurrence of patients during the follow-up period of five years. Utilizing their dosage plan, the model attained a threshold of 2.14 × 10 7 [cells], corresponding to a diameter of 30.14[mm] (see Supplementary Figure S8).…”
Section: Qualitative Comparison To Oncological Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…2. The prospective study of Ersoy et al (87), showed no recurrence of patients during the follow-up period of five years. Utilizing their dosage plan, the model attained a threshold of 2.14 × 10 7 [cells], corresponding to a diameter of 30.14[mm] (see Supplementary Figure S8).…”
Section: Qualitative Comparison To Oncological Studiesmentioning
confidence: 87%
“…In this paper, we propose theoretical explanation for the fact that still, a substantial percentage of patients fail the treatment (38)(39)(40)(41)(42)(43). It is possible that treatment failure results from tumor size, as described in the literature (86,87) and shown in Figure 5, or from an improper selection of the drug dose, m 0 , that is implicitly reflected in the drug instillation rate, m, of the model. In this context, improper is defined as a set of parameters that are theoretically patient-specific and do not meet the conditions required by this mathematical method for cure.…”
mentioning
confidence: 97%
“…A total of nurses attending the courses at the specified dates and who agreed to participate in the study were included in the analysis. Data were collected through a questionnaire that we developed in accordance with current literature on nursing ethics ( 2 - 4 , 8 , 9 ). The questionnaire consisted of two parts and 46 items.…”
Section: Methodsmentioning
confidence: 99%
“…By laying out the liabilities that each individual physician or health practitioner has towards him or herself and his or her patients, applied ethics teaches that physician the behavior that is in line with his or her own values. It assists in the decisions they must make, as well as their fulfillment with the profession; furthermore, it helps them avoid causing patients harm ( 2 , 3 ). The Florence Nightingale Pledge, acknowledged as the first ethical code for the medical profession, included important guidance rules for nurses.…”
Section: Introductionmentioning
confidence: 99%